Penerapan Problem Based Learning dan Pembelajaran Tanggap Budaya untuk Meningkatkan Motivasi Belajar Siswa - I Kadek Sandiase; Gamar Binti Non Shamdas; Jihad Jihad (Cipta Media Harmoni, 2025)
Learning motivation is a key element in achieving optimal learning outcomes. Observations at SMANOR Tadulako Palu revealed that the learning motivation of grade XI B students is still moderate and requires improvement. The purpose of this study was to evaluate the extent to which the implementation of problem-based learning and culturally responsive learning improves learning motivation. This study used a classroom action approach, conducted in two cycles through planning, implementation, observation, and reflection. The instrument used was a learning motivation questionnaire, and the data were analyzed descriptively. There was an increase in student learning motivation, as evidenced by the fact that in the pre-cycle phase, only five students were in the very high motivation category, while in the second cycle, this number increased to thirteen. The combined implementation of problem-based learning and culturally responsive learning has proven effective in increasing learning motivation by creating more contextual, engaging, and relevant learning that reflects students' cultural backgrounds.